2011
DOI: 10.1073/pnas.1109071108
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in fibronectin binding protein A of Staphylococcus aureus are associated with infection of cardiovascular devices

Abstract: Medical implants, like cardiovascular devices, improve the quality of life for countless individuals but may become infected with bacteria like Staphylococcus aureus. Such infections take the form of a biofilm, a structured community of bacterial cells adherent to the surface of a solid substrate. Every biofilm begins with an attractive force or bond between bacterium and substratum. We used atomic force microscopy to probe experimentally forces between a fibronectin-coated surface (i.e., proxy for an implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 52 publications
(52 reference statements)
5
95
1
Order By: Relevance
“…This binding of S. aureus FnBPA to human fibronectin is thought to be a critical initial step in the pathogenesis of prosthetic device infections (577). Lower et al showed that specific single nucleotide polymorphisms in fnbA were associated with (i) greater in vitro binding to fibronectin, as assessed by atomic force microscopy; (ii) a higher number of hydrogen bonds between fibronectin and FnBPA in a simulated model system; and (iii) a higher risk of cardiac device infection (CDI) in patients with SAB (578).…”
Section: Formation Of Biofilmmentioning
confidence: 99%
“…This binding of S. aureus FnBPA to human fibronectin is thought to be a critical initial step in the pathogenesis of prosthetic device infections (577). Lower et al showed that specific single nucleotide polymorphisms in fnbA were associated with (i) greater in vitro binding to fibronectin, as assessed by atomic force microscopy; (ii) a higher number of hydrogen bonds between fibronectin and FnBPA in a simulated model system; and (iii) a higher risk of cardiac device infection (CDI) in patients with SAB (578).…”
Section: Formation Of Biofilmmentioning
confidence: 99%
“…The surfaces of bacteria act as the first line of defense against harmful external stimuli, including antibiotics (Delcour, 2009) and antimicrobial peptides, (Fantner et al, 2010;Sochacki et al, 2011) and also play crucial roles in interacting with other surfaces, including host tissues (Van Houdt and Michiels, 2005) and medical plastics, (Lower et al, 2011) to help bacterial cells attach and colonize. In order to survive in a changing environment, bacteria replicate and evolve quickly, (Carnes et al, 2010;van der Mei and Busscher, 2012) leading to diversity of different bacteria species, and variability within the same species.…”
Section: Introductionmentioning
confidence: 99%
“…The data generated with these bulk assays are averaged over many bacteria, which wash out important variability or heterogeneity of different bacterial cells. Various imaging techniques, such as fluorescence (Cywes--Bentley et al, 2013;Sochacki et al, 2011), AFM (Fantner et al, 2010;Lower et al, 2011) and transmission electron microscopy (TEM) (Cywes--Bentley et al, 2013), and non--imaging microfluidics techniques, such as flow cytometry (Tracy et al, 2010) and micro electrophoresis (van der Mei and Busscher, 2012), have been used to study bacterial surfaces. These techniques have contributed to the understanding of bacteria, but each has disadvantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these new tools, atomic force microscopy (AFM) allows us to analyze the organization, biophysical properties, and interactions of cell-wall molecules directly in single cells (14,15). During the past years, there has been much progress in applying AFM techniques to explore the forces involved in cell adhesion and biofilm formation by staphylococci, down to molecular resolution (16)(17)(18)(19)(20)(21)(22)(23). Here, we used AFM to study the forces guiding the self-association of the S. aureus serine-aspartate repeat protein SdrC (Fig.…”
mentioning
confidence: 99%